Correlations between capnographic waveforms and peak flow meter measurement in emergency department management of asthma. - Nik Hisamuddin, N A R; Rashidi, A; Chew, K S; Kamaruddin, J; Idzwan, Z; Teo, A H (2009)
BACKGROUND